Thermal conductivity of biocemented graded sands - Xiao, Yang (2022)
This paper includes an investigation of the thermal conductivity of biocemented soils to better understanding the regimes of heat transmission through soils treated by microbially induced calcium carbonate precipitation (MICP). A series of thermal conductivity tests using the transient plane source method (TPS) was performed on biocemented silica sand specimens with different gradations, void ratios, and MICP treatment cycles. The results showed that MICP treatment greatly improved the thermal conductivity of sand specimens. An increase in uniformity coefficient or a decrease in void ratio of the sand resulted in an increase in the thermal conductivity of MICP-treated specimens for a given MICP treatment cycle. The increment of thermal conductivity of MICP-treated specimens with respect to that of untreated specimens was also affected by gradation, void ratio, and content of calcium carbonate. The greatest improvements in thermal conductivity were achieved for sands having an initial degree of saturation between 0.82 and 0.85. An empirical equation was established to predict the thermal conductivity of MICP-treated silica sand with different variables, which may be useful in designing energy piles in biocemented sand layers.